Tinjauan Yuridis atas Badan Usaha Milik Desa (BUMDES) Sebagai Badan Hukum - Pafrico R, Randi; Muskibah, Muskibah; Naili Hidayah , Lili (Zaaken: Journal of Civil and Business Law, 2025)
This study aims to analyze the regulation of Village-Owned Enterprises (BUMDes) as legal entities and their liability for third-party losses within the framework of Indonesian legislation. The research employs a normative legal method with statutory and conceptual approaches to examine the synchronization of existing regulations. The findings indicate that when BUMDes are established in the form of a Limited Liability Company (PT), the formation process must comply with two legal frameworks: Government Regulation No. 11 of 2021 on Village-Owned Enterprises and Law No. 40 of 2007 on Limited Liability Companies. Regarding liability, BUMDes as a legal entity are obliged to compensate third-party losses in accordance with legal responsibility principles. However, the scope of liability differs depending on whether the loss arises from the negligence of management or from the fault of the BUMDes itself. This study concludes that the regulation of BUMDes as legal entities, particularly in the form of PT, faces regulatory dualism that may create legal uncertainty. Therefore, a specific regulation is required to comprehensively govern the legal status of BUMDes and their liability mechanisms, thereby strengthening legal certainty and enhancing their role as drivers of rural economic development.